Pengaruh Pemberian Fermentasi Isi Rumen Sapi dan Fermentasi Darah Sapi untuk Media Tumbuh Maggot Black Soldier Fly (BSF) - Nurul Hidayati; Inspirasi S. Chairil (Department of Agribusiness, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2026)
This study aims to evaluate the effectiveness of feeding based on fermented cow rumen contents and fermented cow blood on the growth and nutritional quality of Black Soldier Fly (BSF) maggots as an alternative poultry feed. The material used in this study was Black Soldier Fly (BSF) maggots fed a diet consisting of fermented bovine rumen contents and fermented bovine blood The research method used was a completely randomized design (CRD) with four treatments, namely:P1 (75% fresh watermelon rind and 25% rice bran); P2 (75% fermented bovine rumen contents and 25% rice bran); P3 (75% fermented bovine blood and 25% rice bran); P4 (37.5% fermented bovine rumen contents, 37.5% fermented bovine blood, and 25% rice bran). The parameters observed included maggot growth, mortality, water content, crude protein, crude fiber, and dry weight, dry matter. The results showed that although there was no statistically significant effect on most parameters, treatment P3 provided the best results in increasing fresh weight and dry weight of maggots. Meanwhile, the parameters of water content, dry matter, crude protein and crude fiber did not show significant differences between treatments. Thus, slaughterhouse waste (RPH) such as cow rumen contents and cow blood has high potential to be used as an economical and environmentally friendly feed medium for BSF maggots